2017
DOI: 10.1111/jcpt.12638
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of two tools to screen potentially inappropriate medication in internal medicine patients

Abstract: Internal medicine patients are frequently prescribed PIMs. PIM-Check's PIM detection rate was three times higher than STOPP/START's, and its screening time was shorter thanks to its electronic interface. Nearly half of the PIMs detected were judged to be non-clinically relevant, however, potentially overalerting the prescriber. These tools can, nevertheless, be considered useful in daily practice. Furthermore, the relevance of any PIM detected by these tools should always be carefully evaluated within the clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 38 publications
1
10
0
Order By: Relevance
“…According to our knowledge, this is the first study assessing the concordance and overlap of three distinct PIM-detecting tools EU( 7)-PIM list, 2019 AGS Beers criteria, and STOPP v2 criteria in hospitalized patients. The low overlap and concordance between tools highlight the need to develop a PIM-detecting tool for patients exposed to a high number of PIMs ( ≈ 80%, in all tools used) and reinforce the fact that general internal medicine patients are at risk of PIM (Hudhra et al, 2016;Blanc et al, 2018a;Blanc et al, 2018b). Although being developed for different drug markets and different populations, these criteria are the most used.…”
Section: Discussionmentioning
confidence: 99%
“…According to our knowledge, this is the first study assessing the concordance and overlap of three distinct PIM-detecting tools EU( 7)-PIM list, 2019 AGS Beers criteria, and STOPP v2 criteria in hospitalized patients. The low overlap and concordance between tools highlight the need to develop a PIM-detecting tool for patients exposed to a high number of PIMs ( ≈ 80%, in all tools used) and reinforce the fact that general internal medicine patients are at risk of PIM (Hudhra et al, 2016;Blanc et al, 2018a;Blanc et al, 2018b). Although being developed for different drug markets and different populations, these criteria are the most used.…”
Section: Discussionmentioning
confidence: 99%
“…Eighth, we did not evaluate the preventability of unplanned readmissions. However, a recent study reported that there was no difference in the number of PIMs between hospitalised elderly patients who had experienced an avoidable readmission and those who had not 65. Ninth, an association between disease-specific PIMs66 and unplanned readmissions was not evaluated.…”
Section: Limitationsmentioning
confidence: 99%
“…The first study [21] is the only one performing a comparison between PIM-Check and STOPP/START. In this study, the study population was slightly younger (mean age 77 years), with however 84% of patients aged > 65 years [21], with a mean number of drugs close to our findings (7 drugs per patient). The number of PIP per patient detected by PIM-Check was higher in comparison to our study (6.1 vs 4.2).…”
Section: Discussionmentioning
confidence: 99%
“…PIM-Check was originally designed for patients hospitalized in internal medicine comprising a population with a wider range of age. The current available literature evaluating the use of this tool is composed by three studies [ 21 – 23 ] conducted in internal medicine settings. The first study [ 21 ] is the only one performing a comparison between PIM-Check and STOPP/START.…”
Section: Discussionmentioning
confidence: 99%